The tragedy of smoking, alcohol, and multiple substance use during pregnancy - L T Brink; P E Springer; D G Nel; M D Potter; H J Odendaal (South African Medical Journal, 2022)
Background. Antenatal substance use is a significant public health concern in South Africa (SA). Information on smoking, drinking and drug use during pregnancy was collected prospectively for the Safe Passage Study of the PASS (Prenatal Alcohol in Sudden infant death syndrome and Stillbirth) Network. Objectives. Data from 4 926 pregnant women in a community near Tygerberg Academic Hospital, Cape Town, were examined to determine whether associations between different substance use groups and postnatal infant outcomes at birth and 1 year were significant. Methods. Gestational age (GA) was determined by earliest ultrasound. Maternal data were collected at enrolment or first antenatal visit. Substance use data were obtained at up to four occasions. Birthweight data were derived from medical records, and birthweight z-scores (BWZs) were specifically calculated using INTERGROWTH-21st study data. Statistical analyses were done with Statistica version 13. Results. Women who used more substances enrolled later, were younger, and had smaller mid-upper arm circumferences (MUACs), less education and lower monthly income than women who used no substances (control group). Infants born to women who used more substances had lower GA at delivery, birthweight and BWZ than infants from the control group. At 1 year, infants born to women who used more substances had a lower weight, shorter length and smaller head circumference. Education was positively associated with all infant outcomes at birth and 1 year. MUAC was positively associated with infant BWZ, and weight and length at 1 year. Income was negatively associated with BWZ, but positively associated with all 1-year outcomes. Conclusion. Substance use during pregnancy affects infant outcomes at birth and 1 year of age. The addictive properties of substance use make cessation difficult, so prevention strategies should be implemented long before pregnancy. Higher maternal education, associated with better infant outcomes at birth and 1 year and acting as a countermeasure to substance use, is of paramount importance.